Development of Information Resources in Regional Aspect (Donetsk Region Case Study) - Zakotniuk, O.L. (Економічний вісник Донбасу, 2013)
Territorial quantitative changes in the information component of the regional society were studied in the article. The tendencies and dynamics of information resources development and dissemination were identified and the problems of regional information policy were defined.